The strategic role for TV advertising within integrated communications - Millar, Grant (Henry Stewart Talks, 2009)
TV's role within the broader mix of media, Integrated communications, From interrupt model to engagement model, Consent based communications, What does integrated communications success look like?, The challenge for TV within integrated planning, Benefits of an integrated approach, The relationship between old and new media, Strategic role for TV, The immediate future
Archived at 2022/04/07